The next 10 years in the management of peripheral artery disease: perspectives from The ‘PAD 2009’ conference - Norgren, Lars; Hiatt, W. R.; Dormandy, J. A.; Hirsch, A. T.; Jaff, M. R.; Diehm, Curt; Baumgartner, I.; Belch, J. J. F. (European journal of vascular and endovascular surgery, 2010)
Objectives - To briefly inform on the conclusions from a conference on the next 10 years in the management of peripheral artery disease (PAD). - Design of the Conference - International participation, invited presentations and open discussion were based on the following issues: Why is PAD under-recognised? Health economic impact of PAD; funding of PAD research; changes of treatment options? Aspects on clinical trials and regulatory views; and the role of guidelines. - Results and Conclusions - A relative lack of knowledge about cardiovascular risk and optimal management of PAD patients exists not only among the public, but also in parts of the health-care system. Specialists are required to act for improved information. More specific PAD research is needed for risk management and to apply the best possible evaluation of evidence for treatment strategies. Better strategies for funding are required based on, for example, public/private initiatives. The proportion of endovascular treatments is steadily increasing, more frequently based on observational studies than on randomised controlled trials. The role of guidelines is therefore important to guide the profession in the assessment of most relevant treatment.
Gesehen am 22.05.2023